Analisis Pengaruh Influencer, Kemudahan Transaksi, Dan Affiliate Marketing Pada Keputusan Pemilihan Toko Online - Dafa Hanafi Alifian Fahrezi (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
The development of online stores in Indonesia is getting faster, but every online store is having difficulty getting loyal customers. Based on these circumstances, the research objective is to partially and simultaneously determine the influence of influencers, ease of transactions and affiliate marketing on online shop selection decisions and find interpretations and suggestions for utilizing variables. Field study and literature study research methods, data analysis Validity Test, Reliability Test, Classic Assumption Test, Processing on Multiple Linear Regression, T Test and F Test. Research results The influencer variable (X1) has a significant influence, the ease of transaction variable (X2) has a significant effect. partially has an insignificant influence, the variable Affiliate marketing (X3) partially has an insignificant influence and Influencer (X1), Ease of Transactions (X2), and Affiliate marketing (X3) have a significant influence. Sequentially, the multiple linear regression coefficient is 24.5% for variable X1, 16.6% for variable X2, and 47.7% for variable X3. Variable X3 has the greatest influence of 47.7% on increasing Store Selection Decisions (Y) and variable with various features to support various consumer needs or conditions, and Variable Affiliate marketing (X3) uses strategies that are flexible and easy to adapt.